Investigation of the Copper Requirements of the Metallophyte Liverworts Cephaloziella nicholsonii Douin and C. massalongoi (Spruce) Müll.Frib - Christina Campbell; Daniel L. Kelly; Noeleen Smyth; Neil Lockhart; David T. Holyoak; David Long (Plants, 2023)
Former mine sites can provide habitat for many rare specialised bryophyte species that have adapted to metal-rich soil conditions that are toxic to most other plant species. Some of the bryophyte species found in this habitat are facultative metallophytes, and others are regarded as strict metallophytes, the so-called ‘copper mosses’. It is a general assumption in the literature that Cephaloziella nicholsonii and C. massalongoi, both categorised as Endangered in the IUCN Red List for Europe, are also strict metallophytes and obligate copper bryophytes. This in vitro experiment investigated the growth and gemma production of these two species from different sites in Ireland and Britain on treatment plates of 0 ppm, 3 ppm, 6 ppm, 12 ppm, 24 ppm, 48 ppm and 96 ppm copper. Results show that elevated copper is not an obligate requirement for optimum growth. Differences in response to the copper treatment levels among populations evident within both species could possibly be due to ecotypic variation. A case is also made for the taxonomic revision of the Cephaloziella genus. Implications for the species’ conservation are discussed.